Peruvian industrial fishing before the anchovy (1923-1955) - Maldonado Felix, Hector (2011)
Peruvian industrial fishing had two phases, according to the most exploited species, the first stage was dominated by the bonito (1936-1955) and the second is the time of the anchovy (1955-2010). The transition from the industrial fishing was caused by the participation of national and foreign capitalists (Americans and Europeans) and the Peruvian state. This economic change overcame a series of obstacles in the global context as competition in the U.S. market by Japan and the technological gap (production of canned), and in the local context of interference Guano Management Company, a successful Peruvian-owned company, who was jealous guardian of guanay y piquero, guano birds that depended on the anchovy and sardine